Princípios didáticos para o ensino de evolução biológica na perspectiva da pedagogia histórico-crítica - Pereira, Lucas Monteiro [UNESP] (2015)
Considering the centrality and the importance of the Biological Evolution (EB) theme for the Biology teaching and the detachment of this practice with critical perspectives of education, this work aims to analyze the possibilities of the joint of EB teaching with the theoretical-methodological principles stated by Historical-Critical Pedagogy. It is characterized as a theoretical study, grounded on historical and dialectical materialism. It was appointed, as synthesis, three general didactic principles for the EB teaching on this pedagogical theory's perspective: dialectic conception of transmission-appropriation of the evolutionary theories knowledge; plain commitment with student's worldview formation; and the articulation of didactic components with the specificity of school education. We conclude that these principles may substantiate in different ways on teacher's labor and that other efforts shall sum to this in order to intervene, by the classical knowledge teaching, on the transformation of capitalist social relations